Making a Museum of the Past: Reading A Mind at Peace and The Museum of Innocence Through the Concepts of Museum and City - İmren Gece Özbey (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
One of the main themes in Orhan Pamuk's works is the idea of “making a museum of life,” which represents remembering and preserving in his literary universe. This theme is not only present in The Museum of Innocence, but also appears as a core idea in the author’s preceding novels, especially those set in the Istanbul of his period. This idea reaches its peak when the author simultaneously releases his novel The Museum of Innocence and an eponymous museum. Although Pamuk’s novel-museum project emphasizes the story of the individual, the “home-museum”, as a history of personal events, objects and emotions, as opposed to the official historical discourse and official museums, his project also displays the city of Istanbul and details of its social history. Thus, the novel also turns into a “city-museum”. It is notable that Pamuk credits the idea of making a museum of the past to Ahmet Hamdi Tanpınar and his novel A Mind at Peace in an 1995 article. It can be claimed that there are significant analogies between these two novels. One of them is the place where the beloved woman, who is fictionalized as a work of art or transformed into a work of art, stands in the triangle of museum-city-novel. In this article, A Mind at Peace and The Museum of Innocence will be discussed and criticized through the concepts of museum, city, social history, loss and preservation, as well as examining the idea of making a museum of their Istanbul in these two novelists.